2013
DOI: 10.1111/dom.12055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of sitagliptin with pioglitazone in Japanese type 2 diabetic patients: the COMPASS randomized controlled trial

Abstract: Sitagliptin was not only more tolerable, but also more effective than pioglitazone in Japanese type 2 diabetic patients who had been treated with metformin and/or sulphonylurea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 40 publications
6
36
2
Order By: Relevance
“…Among the 1332 patients enrolled in this study, 826 patients have been taking sitagliptin for 24 months and HbA1c <7.0% (<53 mmol/mol) was achieved in 387 patients (46%). A significant increase in Cr, albeit within normal limits, have been reported in clinical studies in Japan [3,5]. On the other hand, elevation of Cr level was not reported in any of the previous studies carried out to evaluate the influence of sitagliptin on the renal function, including meta-analyses conducted in Western countries [6,7].…”
Section: Discussionmentioning
confidence: 91%
“…Among the 1332 patients enrolled in this study, 826 patients have been taking sitagliptin for 24 months and HbA1c <7.0% (<53 mmol/mol) was achieved in 387 patients (46%). A significant increase in Cr, albeit within normal limits, have been reported in clinical studies in Japan [3,5]. On the other hand, elevation of Cr level was not reported in any of the previous studies carried out to evaluate the influence of sitagliptin on the renal function, including meta-analyses conducted in Western countries [6,7].…”
Section: Discussionmentioning
confidence: 91%
“…However, it is unclear what effect the usual clinical dose of sitagliptin might have on lipid metabolism. Generally, there is no agreement about the changes of lipid parameters after administration of sitagliptin, although decreases of TC, TG and non-HDL-C have been reported in clinical studies [14-17]. …”
Section: Introductionmentioning
confidence: 99%
“…The DPP-4 inhibitors block the rapid inactivation of GLP-1 and improve glycaemic control [13]. It has been indicated that dipeptidyl peptidase-4 inhibitors (DPP4i) are superior to traditional oral hypoglycemic agents in terms of the efficacy and tolerability [14-17]. Such priority can be also seen from the rising status in the authoritative guideline for preventing and treating diabetes.…”
Section: Introductionmentioning
confidence: 99%